Rare earth double perovskites: a fertile soil in the field of perovskite oxides. Issue 9 (24th July 2019) - Chen, Xiaoyun; Xu, Jun; Xu, Yueshan; Luo, Feng; Du, Yaping
Abstract : This review summarizes the compositions, syntheses, and applications of rare earth A2 B′B′′O6 double perovskites. Abstract : Tuning the composition of perovskite oxides results in double perovskites with cation ordering. One of the most important families of double perovskites is A2 B′B′′O6 . With great structural variability, A2 B′B′′O6 are promising candidates for a broad range of applications such as magnetic, optical, electrical, and catalytic applications. Rare earth elements, as the ensemble of fifteen lanthanide elements as well as yttrium and scandium, represent an important part of the periodic table due to their unique 4f electrons. The incorporation of rare earth elements into double perovskites may open great opportunities to novel properties and applications. A significant number of rare earth A2 B′B′′O6 double perovskites have been reported. However, there is no systematic overview of these materials to date. In this review, we summarize the compositions, syntheses, and applications of rare earth A2 B′B′′O6 double perovskites. We hope that it will encourage more researchers to enter this emerging area.